Organically derived exosomes as carriers of anticancer drugs and imaging agents for cancer treatment. (November 2022) - Srivastava, Akhil; Rathore, Shipra; Munshi, Anupama; Ramesh, Rajagopal
Graphical abstract: Abstract: Extracellular vesicles (EVs), is the umbrella term used for different types of vesicles produced by the cells, among which exosomes form the largest group. Exosomes perform intercellular communication by carrying several biologics from donor or parental cells and delivering them to recipient cells. Their unique cargo-carrying capacity has recently been explored for use as delivery vehicles of anticancer drugs and imaging agents. Being naturally produced, exosomes have many advantages over synthetic lipid-based nanoparticles currently being used clinically to treat cancer and other diseases. The finding of the role of exosomes in human diseases has led to numerous preclinical and clinical studies exploring their use as an amenable drug delivery vehicle and a theranostic in cancer diagnosis and treatment. However, there are certain limitations associated with exosomes, with the most important being the selection of the biological source for producing highly biocompatible exosomes on a large scale. This review article explores the various sources from which therapeutically viable exosomes can be isolated for use as drug carriers for cancer treatment. The methods of exosome isolation and the process of loading them with cancer therapeutics and imaging agents are also discussed in the follow-up sections. Finally, the article concludes with future directions for exosome-based applications in cancer diagnosis and treatment.